Reusing Postmodern Heritage: How Literary Theories Can Help - Maxime Coq; Claudine Houbart (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
With the resurgence of interest in postmodern architecture and the need to preserve its built heritage, the challenge arises of effectively updating postmodern buildings without compromising their architectural values. Drawing on examples such as the Hood Museum of Art’s transformation and expansion, this paper highlights the pitfalls of misunderstanding postmodern architecture and proposes a novel approach utilizing literary theories to navigate the complexities of postmodern language. Specifically, the paper delves into the concepts of intertextuality and hypertextuality, derived from Gerard Genette's literary theory, as well as isotopy and allotopy, defined by Algirdas Julien Greimas in the 1960s. These are applied to unravel the subtle nuances of postmodern architectural references, hints, and allusions across a range of examples. By using literary theories as analytical tools, this paper advocates for a deeper understanding of postmodern architecture and suggests that mastering its language is essential for effective engagement and for shaping future interventions.